Spatial Impact of Nitrogen Fertilizer Residue on the Biotic Environment of Rice Field Irrigation Channels - Wantasen, Sofia; Jooudie N. Luntungan; Roni Koneri; Selvie Tumbelaka; Jacqueline Joseph; Junivia Virginia Jermias (Jurnal Pendidikan IPA Indonesia, 2025)
This study aims to analyze the spatial distribution of the impact of nitrogen residue/diversification on the diversity of aquatic biota and contribute to the management of aquatic ecosystems as a source of life. Water quality sampling was carried out by grab sampling with water quality parameters measured including total nitrogen (TN), ammonia (NH₃), nitrate (NO₃⁻), and nitrite (NO₂⁻). TN analysis was carried out using the Total Kjeldahl Nitrogen (TKN), nitrate, and nitrite calculation methods. NH₃ was measured using the Flow Injection Analysis method, while NO₃⁻ was analyzed using the Cadmium Reduction Method and NO₂⁻ with the colorimetric method.Plankton sampling was done by filtering 20 liters of water from the surface layer using a 2-liter bucket. The plankton species diversity index was calculated using the Shannon-Wiener Index method. The effect of environmental factors on nitrogen chemical fertilizer residues in each research location was analyzed using the Principal Component Analysis (PCA). The results showed an increase in ammonia and nitrite residues followed by a decrease in total nitrogen and nitrate concentrations. Seven classes and 22 plankton species were identified, consisting of 18 phytoplankton species and four zooplankton species. The dominant plankton came from Cyanophyceae, Bacillariophyceae, and Chlorophyceae. The highest plankton species diversity index was recorded in Irrigation IX and VII. Based on the study results, plankton diversity at the research location is included in the moderate category. The main environmental factors that influence the presence of plankton in irrigation channels are the concentration of nitrate and nitrogen in the water.